Assessment of parotid gland masses with B-mode ultrasonography and strain elastography findings - Öğüşlü, Umut; Aydın Aksu, Sibel; Uyanık, Sadık Ahmet; Gümüş, Burçak (Journal of Surgery and Medicine, 2019)
Aim: Ultrasound elastography (USE) has been found useful in differentiation between malignant and benign lesions of various tissues, such as the thyroid, breast, lymph node and prostate, however, there is limited data on the parotid gland. The aim of this study is to assess the diagnostic performance of B-mode ultrasonography (US) and USE findings in differentiating between benign and malignant parotid gland masses. A secondary goal is to evaluate results for the most frequent benign lesions. Methods: In this cross-sectional study, 57 masses in 48 patients were evaluated. 2 radiologists examined each patient. B-mode US (size, contour, skin depth, internal structures, calcification, cystic component) and USE (a semiquantitative value strain index (SI)) findings were noted. We considered each feature individually. All patients underwent fine needle aspiration cytology (FNAC) and surgical resection. Results: 50 masses were benign and 7 were malignant. Among B-mode US results, contour irregularity was found to have the highest accuracy (85.7%) in differentiating malignant lesions. When USE findings were considered, intra-observer agreement was moderate to fair and interobserver agreement was moderate. Malignant masses had mildly high SI scores. There was a wide range overlap between malignant and benign lesions. There was no statistically significant difference (P=0.422) and we could not attain a reliable SI cut-off value. Conclusion: Despite the promising results of USE in breast and thyroid lesions, conventional US findings and FNAC are still the primary diagnostic tool to evaluate parotid lesions.